Anaerobic co-digestion of septage and food waste simple batch and two-phase reactor systems - Lingating, Reuben Dasay Jr (2012)
This study determined the viability of septage and food waste as co-substrates for anaerobic digestion. It was divided into three parts. The first part focused on the determination of the effects of varying the mixture ratio of the co-substrates to the digestion performance of simple batch reactors. Feedstock with food waste-to-septage ratios (%v/%v) of 0:100, 30:70, 50:50, 70:30 and 100:0 were loaded into batch reactors and were digested for 24 days. Throughout the period, the methane generation was monitored and samples were collected for testing of total and dissolved chemical oxygen demand (TCOD and DCOD), total solids (TS) and volatile solids (VS). the 70:30 digestion run had the highest methane production and obtained a methane yield of 92.0 mL g-1. It also had the highest %VS removal, % TCOD removal, and first-order hydrolysis rate constant of 44.1%, 24.7% and 0.1462 day-1, respectively. The second part of the study dealt with the determination of the effects of increasing the seed sludge added with 50% more to the 70:30 digestion run. THe methane production increased by 55.2%,thereby increasing the methane yield to 137.8 mL g-1. The %VS and %TCOD removals were also increased to 56.1% and 36.6% respectively. The hydrolysis step of the 70:30 feed mixture digestion was not significantly improved at greater amount of inoculum added, with the first-order hydrolysis rate constant only slightly increased to 0.1542 day -1